Pengaruh Sertfikasi Halal, Kesadaran Halal dan Bahan Makanan Terhadap Minat Beli Produk Makanan Halal (Studi Kasus Masyarakat Muslim di Kota Banjar) - Cupian Cupian; Kintan Meilasari; Sarah Annisa Noven (ITB AAS INDONESIA Surakarta, 2023)
This exploration means to know the impacts of halal confirmation, halal mindfulness and food fixings in keen on purchasing halal food items in Islamic communitys in Banjar city. the lord of exploration useng in this examination is the quantitative investigation. Dat in this investigation utilizing essential information assortment methods of examination and polls. The example in this examination is 314 respondens. Sampel assortment strategies in this examination utilizing non probality testing. Investigation of this examination utilizing different straight regresion tests. Based on partial data analysis, there is a positive and significant impact on halal certification,halal awarenenss and food ingredients in interested in buying halal food products in Islamic communitys in Banjar city. The result of this study indicate the R2 value of 0.773 or 77,3%. The meaning of these coefficient’s effects will affect halal certification, halal awareness and food ingredients against the buying interenst variable is 77,3%. While the other 22,7% influenced by other variables.